Involvement of Fcα/μR (CD351) in autoantibody production - Yoshizawa, Yuichi; Honda, Shin-ichiro; Shibuya, Akira (Molecular immunology, 2014)
•Fcα/μR enhances, rather than suppresses, autoantibody production.•Fcα/μR on the MRL/MpJ-Faslpr/lpr background mice decreased survival rate.•IgM prevents autoantibody production independently with Fcα/μR expression. Antibody exerts various immune responses via binding to Fc receptors expressed on immune cells. Although several reports have demonstrated that IgM prevents autoantibody production, the role of IgM Fc receptors is largely unknown. To analyze the involvement of Fcα/μR (CD351), an Fc receptor for IgM and IgA expressed on B cells and follicular dendritic cells (FDCs), in IgM-mediated suppression of autoantibody production, we generated mice deficient in Fcα/μR on the background of MRL/MpJ-Faslpr/lpr (Fcamr−/−Faslpr/lpr) mice. Fcamr−/−Faslpr/lpr mice showed significantly lower titers of IgG autoantibodies against double strand (ds) DNA, histone and cardiolipin in the sera than did Fcamr+/+Faslpr/lpr mice. Moreover, Fcamr−/−Faslpr/lpr mice showed higher survival rate at the ages of 28, 32 and 40 weeks old, compared with Fcamr+/+Faslpr/lpr mice. These results suggest that Fcα/μR enhances, rather than suppresses, autoantibody production.